The essentials of instructional design connecting fundamental principles with process and practice - Brown, Abbie (Prentice Hall, 2011)
The Essentials of Instructional Design is designed to introduce the essential elements of instructional design (ID) to students who are new to ID. The key procedures within the ID process are covered in complete chapters that introduce and describe the procedure, with examples of how the procedure is accomplished using the best known instructional design models. Unlike most other ID books, this book provides an overview of the principles and practice of ID without placing emphasis on any one ID model. --from publisher description.